KARAKTERISASI PENAMBAHAN KITOSAN DAN HAP PADA PLA TERHADAP SIFAT MEKANIK KOMPOSIT - Serfandi, Dina Novera; Setyarini, Putu Hadi; Purnami, Purnami; Sulistyono, Sulistyono (Jurnal Rekayasa Mesin, 2024)
PLA (poly lactid acid) is a biodegradable polyester that can be applied to tissue engineering because it is biocompatible and non-toxic. The purpose of this study to determine the mechanical characteristics of mixing PLA, chitosan, and Hydroxyapatite. There were 4 variations in this study, namely PLA 100 (pure PLA), PLA-chitosan-Hydroxyapatite 94-3-3 (Mix 1), PLA-chitosan-Hydroxyapatite 94-0-6 (Mix 2), PLA-chitosan-Hydroxyapatite 94-6-0 (Mix 3). The method of processing specimens is carried out by mixing the material using an extrusion machine to form filaments, then the filaments are cut to a size of 3-5 mm for injection processing with a process temperature of 170-190°C and an injection pressure of 5 Bar. The tensile strength value of the composite decreased by 0.14% from the tensile strength value of pure PLA it’s cause of the characteristic of chitosan and HAp were stiff and brittle.